Until the End of Time: Mind, Matter, and Our Search for Meaning in an Evolving Universe by Brian Greene - Williams III, George Robert (Journal of Scientific Exploration, 2021)
Brian Greene’s Until the End of Time: Mind, Matter, and Our Search for Meaning in an Evolving Universe, as the title suggests, is an ambitious work. Greene takes the reader on a vast tour which begins with the birth of the universe and ends with its (likely) dissolution. The staggering timescale that Greene considers here is perhaps unique among science books aimed at a wide audience. And Greene uses the backdrop of the universe’s emergence and demise as an effective platform to explore human meaning in a relatively wide range of inquiry. These subjects include consciousness, religion, language, and the arts. It appears significant for Greene that these, as important as they are, all play out in a relatively brief time in the context of the evolution and demise of the universe. At the end of the day, Greene submits that life is likely ephemeral. He provides a quote from Nabokov that characterizes human life as a “brief crack of light between two eternities of darkness.” (p.13)